Geology of the Atacocha mine, department of Pasco, Peru - Johnson, Robert Francis (1955)
The Atacocha lead-zinc mine, 15 km northeast of Cerro de Pasco in Central Peru, was the object of a detailed geologic investigation in 1952 by geologists of the Instituto Nacional de Investigación y Fomento Minero and the U.S. Geological Survey. The mine is about 4,000 m above sea level, in an area of steep topography with about 900 m of relief. Rocks exposed at Atacocha consist of limestone, chert breccia, quartz sandstone, and basalt that range from Late Triassic to Early Cretaceous in age. These rocks have been intruded by dacite of probable Tertiary age. The most prominent structural features are the east limb of a large anticline east of the mine, and a south-plunging syncline to the west. The two folds are separated by a major fault zone. The rocks west of the fault have been dragged along it and are bent into a small cross fold, which seems to be the primary control for the localization of the ore. The main structural feature in the mine is a reverse fault on which limestone has been thrust over quarts sandstone. The Atacocha mine contains about 30 km of underground workings on 16 levels, spaced over a vertical distance of 700 m. The working explores portions of a reverse fault and follow veins in limestone and sandstone. Production was 600 tons of ore per day in late 1953. Ore occurs in veins filling tension fractures in limestone and sandstone near the axis of the cross fold and in irregular replacement bodies in a narrow limestone horizon above and close to the reserve fault. Replacement bodies are also found west of the syncline in limestone close to the contact between limestone and overlying chert breccia. The typical sulfide mineral association is galena, sphalerite, and pyrite, with minor chalcopyrite and jamesonite. Gangue minerals other than pyrite are calcite, rhodochrosite, clay minerals, and a minor amount of fluorite. Late veins of realgar and orpiment cut the ore minerals. Very little oxidation or supergene enrichment has taken place.